Development of Microlearning Video Media for Manufacturing Technical Drawing Learning Assisted by AI Adam CAD at SMK Negeri 52 Jakarta - Syava Aisya Kamila; C. Rudy Prihantoro; Hari Din Nugraha (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2026)
This study aims to develop and assess the feasibility of AI Adam CAD-assisted microlearning video media for Manufacturing Technical Drawing learning at SMK Negeri 52 Jakarta. The study employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, Disseminate), with the scope limited to the Develop stage. The developed product consists of microlearning videos covering 3D model creation using AI Adam CAD and technical drawing production using Autodesk Inventor, delivered through a web-based platform. Feasibility was evaluated by a content expert, a media expert, and Grade XI Machining Engineering students through questionnaires. Results indicate that the content expert rated the media at 97% (Very Feasible), the media expert at 96% (Very Feasible), and student responses reached 94% (Very Feasible). These findings confirm that the developed media meets feasibility criteria as an independent learning support tool for Manufacturing Technical Drawing at the vocational secondary level. Subsequent studies are encouraged to carry out the Disseminate phase in full and assess the media's effectiveness through an experimental design.